2018
DOI: 10.1177/0269215518790632
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and feasibility of acupuncture for knee osteoarthritis: a pilot randomized controlled trial

Abstract: It showed that three sessions per week acupuncture intervention of knee osteoarthritis was feasible and safe. No difference was observed between groups due to small sample size. Larger (sample size ⩾ 296) randomized controlled trials of this intervention appear justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 32 publications
0
52
0
Order By: Relevance
“…It is also considered a potential non-pharmacologic intervention to prevent or to slow KOA progression although clinical guidelines have contradictory views [8,9]. Our previous pilot study also showed that MA (three sessions per week for eight weeks) is more feasible and safe compared with sham acupuncture for patients with KOA [10]. Since acupuncture was known to reduce systemic concentrations of pro-inflammatory cytokines, the anti-inflammatory effect are suggested as a potential working mechanism.…”
Section: Introductionmentioning
confidence: 96%
“…It is also considered a potential non-pharmacologic intervention to prevent or to slow KOA progression although clinical guidelines have contradictory views [8,9]. Our previous pilot study also showed that MA (three sessions per week for eight weeks) is more feasible and safe compared with sham acupuncture for patients with KOA [10]. Since acupuncture was known to reduce systemic concentrations of pro-inflammatory cytokines, the anti-inflammatory effect are suggested as a potential working mechanism.…”
Section: Introductionmentioning
confidence: 96%
“…8,9 Our previous pilot study also showed that MA (three sessions per week for 8 weeks) is more feasible and safe compared with sham acupuncture for patients with KOA. 10 Since acupuncture was known to reduce systemic concentrations of pro-inflammatory cytokines, the anti-inflammatory effect is suggested as a potential working mechanism. For example, EA at the ST36 acupuncture point reduced the lipopolysaccharide (LPS)-induced serum levels of cytokines TNF-α, monocyte chemotactic protein-1 (MCP-1), and this anti-inflammatory mechanism mediated by the sciatic and vagus nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of a previous trial [16], the response rates of EA, MA and SA group are assumed to be 70%, 60% and 40%, respectively. With a 2-sided significance level of 2.5% and power of 80%, 128 participants in each group will be required to detect a difference as small as 20% between each acupuncture group and control group.…”
Section: Sample Sizementioning
confidence: 99%
“…Based on previous pilot trial [16], high-dose acupuncture (24 sessions in 8 weeks) may be an effective option for knee osteoarthritis. Electro-acupuncture (EA) combines manual acupuncture (MA) with electric stimulus [17].…”
Section: Introductionmentioning
confidence: 99%